Psychometrics of the questionnaire on the intention to use medicinal plants in patients with type 2 diabetes based on the developed theory of planned behavior - Batool Yamani Ardakani; Vali Bahrevar; MoradAli Zareipour; Mojtaba Fattahi Ardakani; Razieh Nabimeybodi (Journal of Education and Health Promotion)
BACKGROUND: Using medicinal plants as a complementary medicine in patients with diabetes with the aim of controlling the disease and managing its complications is increasing worldwide. Despite the widespread use of these types of drugs, the reasons for their use have not been investigated based on the theory of planned behavior. The present study was conducted with the aim of psychometrics of the questionnaire on the intention to use medicinal plants in patients with type 2 diabetes based on the theory of planned behavior (TPB). MATERIALS AND METHODS: In this descriptive cross-sectional study, as many as 622 diabetic patients, referring to Yazd Research Center for Diabetes, were selected and included in the study by convenience sampling method based on the inclusion criteria defined for the study in 2022. The researcher’s data collection tool was a questionnaire developed based on the TPB. Data analyzed via confirmatory factor analysis method using Smart PLS software (partial least squares structural equation modeling [PLS-SEM]) was used to confirm the structure of the questionnaire. RESULTS: The questions of TPB constructs were examined using convergent validity criteria (AVE = 0.57–0.74) and discriminant validity using the Fronell–Larcker criterion and were confirmed. The reliability of TPB constructs was also measured within the approved range (rhoC = 0.86–0.95). Using the PLS-SEM algorithm approach, there is a significant relationship between the constructs of abstract norm (β =0.44, P < 0.001), perceived behavioral control (β =0.25, P < 0.001), and attitude (β =0.1, P = 0.006) with intention; the construct of abstract norm was recognized as the most important predictor of intention in using medicinal plants. CONCLUSIONS: The results of this questionnaire emphasize the importance of perceived norms, perceived behavioral control, and attitude in the inclination of patients with diabetes toward the use of herbal medicines. Thus, this tool can be used to measure diabetic patients’ intention for using medicinal plants.